Pemanfaatan Artificial Intelligence dalam Hukum Acara Pidana: Tinjauan Yuridis dan Dampak Sosial - Septiawan, Rendi; Anandatia, Via; Gustina, Adin (Universitas Sains dan Teknologi Komputer, 2024)
The integration of Artificial Intelligence (AI) into criminal procedure law has emerged as a significant development in enhancing the efficiency and accuracy of judicial systems. However, the implementation of AI in Indonesia remains at an early stage, with challenges such as regulatory gaps, societal trust issues, and potential algorithmic biases. This study aims to explore the potential and challenges of utilizing AI within Indonesia’s criminal procedure framework, focusing on its legal and social implications. Employing a qualitative research approach, this study combines in-depth interviews with legal experts, practitioners, and AI developers, alongside a comprehensive literature review of existing laws and academic research. The findings reveal that AI has the potential to expedite case management, enhance evidence analysis, and reduce human biases in judicial decision-making. Nevertheless, the lack of specific regulations governing AI’s use in the judiciary and the limited public trust pose significant hurdles to its effective implementation. The study also highlights the importance of adaptive legal frameworks and public education to foster transparency and accountability in AI applications. These results contribute to the broader discourse on AI integration in legal systems, particularly in developing countries, by emphasizing the need for localized strategies that address unique social and legal contexts. The implications of this research extend to policymakers and technology developers, providing insights into the regulatory and ethical considerations required for sustainable AI adoption in judicial processes. Future research is recommended to expand the scope of empirical studies and include quantitative analyses to further substantiate the findings.